Garis Dalam Seni Patung - Mr. Soewardi (Ars: Jurnal Seni Rupa dan Desain, 2011)
Line is an element commonly found in any kind of visual arts, both two and three dimensional forms such as painting and sculpture for instance. But basically there’s a different visualization between lines  in painting and lines in sculpture caused by the nature of the dimension. So it leads to the different  way of treating them. This essay is to analyze, mainly, the lines in sculpture relating to its formal structure which covers several types of style.Keywords: line, sculpture